The influence of moral sensitivity on organizational cooperation. Issue 6 (1st June 2015) - Terán, Oswaldo; Sibertin-Blanc, Christophe; Gaudou, Benoit
Abstract : Purpose: – The purpose of this paper is to present how to model moral sensitivity and emotions in organizational setting by using the SocLab formal framework. SocLab is a platform for the modelling, simulation and analysis of cooperation relationships within social organizations – and more generally Systems of Organized Action. Design/methodology/approach: – Simulation results, including an interesting tendency for a Free Rider model, will be given. Considering that actors' decision-making processes are not just driven by instrumental interest, the SocLab learning simulation algorithm has been extended to represent moral sensitivity, making actors trying to prevent bad emotions and feel good ones. Findings: – Some simulation results about actors' collaboration and emotions in a Free Rider model were presented. A noteworthy tendency is that actors' unconditional collaboration, which occurs when their moral sensitivity reaches its highest value, is not so good since it exempts other actors from collaboration (they take advantage from the unconditional collaboration), while values of moral sensitivity somewhat below the highest value (between 0.7 and 0.9) still induces collaboration from others. Originality/value: – The research and results presented in this paper have not been presented in other papers or workshops. The presented quantitative definition of emotions (determining indexes of emotions) is different to previous approaches – for instance, to Ortony, Clore and Collins (OCC) qualitative descriptions and to logical descriptions. Similarly, simulation of morality in organizations is a new research field, which has received scarce attention up to now.